THE ROLE OF LIBRARY OUTREACH PROGRAMS IN INCREASING READING INTEREST IN REMOTE COMMUNITIES - Surbakti, Khoirunnisa; Harahap, Annur Rosida; Hasibuan, Silva Lestari (PERSPEKTIF: Journal of Social and Library Science, 2025)
Reading is a fundamental pillar in the development of a highly skilled human resource base. However, reading interest in Indonesia remains low, particularly in remote areas that face several challenges, such as limited access to reading materials, insufficient library facilities, and a lack of effective literacy programs. This study examines the strategic role of library outreach programs in addressing these challenges. These programs encompass mobile libraries, literacy training, and the use of digital technologies to reach communities that have previously struggled to access library services. Using a qualitative descriptive approach based on a literature review, the study demonstrates that outreach programs can broaden access to information, foster early literacy development in children, and enhance community engagement. In this way, libraries evolve from mere book repositories into catalysts for social change, contributing to the creation of an educated, information-literate, and empowered society, particularly in remote regions.